Editorial: International Business in Latin America & Caribbean: Contexts and Implications - Floriani , Dinorá Eliete; Vasconcellos, Sílvio Luís de; Amal , Mohamed; Perez , Maria Alejandra Gonzalez (Internext, 2023)
editorial